Electrical Characterization of Self-Assembled 1D Gold Nanoparticle Chains : Implications for Chemiresistor Sensors - Schupp, Stefan; Schupp, David Joshua; Hilbert, Holger; Schwarz, Emil; Köser, Rebecca; Cölfen, Helmut; Schmidt-Mende, Lukas (My University, 2024)
The introduction of dipoles on gold nanoparticle surfaces provides the formation of chain-like nanoparticle assemblies in solution under ambient conditions. Here, we present studies on influencing and controlling the strength of the induced dipole by thiols. Aromatic thiols lead to enhanced surface dipoles, where electron-donating functions can further increase the interaction. Thereby, particle–particle distances and chemical environment at the particle interface were manipulated, which resulted in different tunneling resistances Rg in these 1D structures. Here, Rg seemed to be mostly dominated by the interparticle distance rather than the type of ligand. Temperature-dependent current–voltage measurements of thiol-bearing nanoparticle chains revealed two different transport mechanisms. For temperatures <170 K, a thermally activated electron tunneling takes place, which depends on the charging energy Ec. Whereas for higher temperatures, a transition to an electron hopping process occurs determined by the involved thiol and nanoparticle shape. For structures with strong interparticle electronic coupling, the conduction mechanism is almost temperature-independent, which makes them promising candidates for highly sensitive chemiresistor sensors.
Keywords: 530